Can't stand losing you [videorecording (DVD)] : surviving the Police - Summers, Andy; Summers, Andy (Cinema Libre Studio, 2015)
Follows guitarist Andy Summers journey from his early days in the psychedelic '60s music scene, when he played with the Animals, to chance encounters with drummer Stewart Copeland and bassist Sting, which led to the formation of a punk trio, the Police. During the band's phenomenal rise and its dissolution at the height of their popularity in the mid-80s, Summers captured history with his candid photographs. Utilizing rare archival footage and insights from the guitarist's side of the stage, the film brings together past and present as the band members reunite, more than two decades later, for a global reunion tour in 2007.